All‐Solution‐Processed Top‐Emitting InP Quantum Dot Light‐Emitting Diode with Polyethylenimine Interfacial Layer - Youngwoo Jeon; Soobin Sim; Doyoon Shin; Wan Ki Bae; Hyunkoo Lee; Hyunho Lee (Advanced Electronic Materials, 2024)
Abstract Recent studies on top‐emitting structure, which is designed to enhance the color purity and outcoupling efficiency of quantum‐dot light‐emitting diodes (QLEDs), employ commercially unviable methods owing to limited options for applying the hole injection layer through solution processes on the bottom electrode. In this study, all‐solution‐processable conventional top‐emitting QLEDs (TQLEDs) are successfully fabricated by introducing a polyethylenimine (PEI) interlayer, doping isopropyl alcohol (IPA) into the hole‐injection layer (poly (3,4‐ethylenedioxythiophene):poly(4‐styrenesulfonate), PEDOT:PSS), and using the dynamic spin‐coating method. The increased hole injection resulting from the tuned anode‐HIL interface by the PEI and IPA‐doped HIL, coupled with the enhanced outcoupling efficiency and full width at half maximum (FWHM) derived from the optimized cavity length through simulation, realizes a red InP QLED with high efficiency and color purity. The optimized TQLED exhibits a maximum current efficiency and FWHM of 28.04 cd A−1 and 36 nm, respectively, which are threefold higher and 8 nm narrower than those of bottom‐emitting QLEDs, marking the highest current efficiency ever reported for top‐emitting red InP QLEDs.